Pembimbingan Mahasiswa dalam Pemberdayaan Masyarakat Desa Lantan melalui Kegiatan Himatika Mengabdi Tahun 2024 - Primajati, GIlang; Kurniawan, Eka; Supiarmo, M.Gunawan; Junaidi, Junaidi; Oktavihari, Dita; Amrullah, Amrullah (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The HIMATIKA Mengabdi 2024 Mentorship Program is a form of community service carried out by lecturers and students of the Mathematics Education Study Program at the University of Mataram in Lantan Village. The main objective of this activity is to enhance students' social awareness and contribute meaningfully to the fields of education, health, and community empowerment. The program included various initiatives such as HIMATIKA Goes to School (HGTS), revitalization of the Creative Park, teaching at the TPQ (Qur'anic Learning Center), stunting awareness campaigns, health check-ups, community clean-up activities, and a cultural night celebration. The results show that active student participation successfully increased students’ motivation to learn, raised community awareness about the importance of nutrition and health, and strengthened social ties among residents. These outcomes were analyzed using the Experiential Learning and Community Empowerment approaches to explain the impact of interdisciplinary student involvement in community service. This program demonstrates that integrating academic knowledge into community service can be an effective learning medium for students while simultaneously generating sustainable positive impacts for rural communities.